Caries Detection around Restorations Using ICDAS and Optical Devices - Diniz, Michele Baffi; Eckert, George Joseph; González-Cabezas, Carlos; Cordeiro, Rita De Cássia Loiola [UNESP]; Ferreira-Zandona, Andrea Gonçalves (Wiley, 2016)
Purpose Secondary caries is the major reason for replacement of restorations in operative dentistry. New detection methods and technology have the potential to improve the accuracy for diagnosis of secondary carious lesions. This in vitro study evaluated the performance of the ICDAS (International Caries Detection and Assessment System) visual criteria and optical devices for detecting secondary caries around amalgam and composite resin restorations in permanent teeth. Materials and Methods A total of 180 extracted teeth with Class I amalgam (N = 90) and resin composite (N = 90) restorations were selected. Two examiners analyzed the teeth twice using the visual criteria (ICDAS), laser fluorescence (LF), light-emitting diode device (MID), quantitative light-induced fluorescence system (QLF), and a prototype system based on the Fluorescence Enamel Imaging technique (Professional Caries Detection System, PCDS). The gold standard was determined by means of confocal laser scanning microscopy. Results High-reproducibility values were shown for all methods, except for MID in the amalgam group. For both groups the QLF and PCDS were the most sensitive methods, whereas the other methods presented better specificity (p < 0.05). Conclusion All methods, except the MID device appeared to be potential methods for detecting secondary caries only around resin composite restorations, whereas around amalgam restorations all methods seemed to be questionable. Clinical Significance Using Internal Caries Detection and Assessment System (ICDAS), an LF device, quantitative light-induced fluorescence and a novel method based on Fluorescence Enamel Imaging technique may be effective for evaluating secondary caries around composite resin restorations.